PEMBERIAN VIDEO TERHADAP SIKAP IBU BAYI TENTANG DETEKSI DINI PERTUMBUHAN DAN PERKEMBANGAN BAYI - Vina Nurul Utami; Riza Amalia (POLTEKKES KEMENKES SEMARANG, 2019)
Many children are found to experience growth and development delays caused by a lack of caring parents in the early detection of growth and development. Health education can make a change of attitude. The purpose of this study was to determine the effect of video on maternal attitudes regarding early detection of growth and development in infants. The method used is pre-experimental design with pretest-posttest. The sample of this study was mothers who had 30 babies with cluster sampling. One group first observes their attitude and then is given a video at the beginning of the meeting, the material is given through strength points, videos and leaflets after that every day using video via WhatsApp and observing again after 2 weeks. The results obtained are different test with Wilcoxon test obtained p-value 0.008, it means that there are differences in attitude before and after exposure to a video about early detection of growth and development of infants. And the conclusion in this study is the provision of health education, videos that can change the attitude of mothers regarding the early detection of growth and development in infants significantly. It is hoped that policy makers will provide training facilities for early detection of children's growth and development for health workers and cadres so that they can be widely applied to children, especially infants.